Longitudinal Blood Pressure Changes and Kidney Function Decline in Persons Without Chronic Kidney Disease: Findings From the MESA Study. (5th October 2017) - Judson, Gregory L; Rubinsky, Anna D; Shlipak, Michael G; Katz, Ronit; Kramer, Holly; Jacobs, David R; Odden, Michelle C; Peralta, Carmen A
Abstract: BACKGROUND: While changes in blood pressure (BP) are independently associated with cardiovascular events, less is known about the association between changes in BP and subsequent changes in renal function in adults with an estimated glomerular filtration rate (eGFR) of >60 ml/min/1.73 m 2 . METHODS: The present study included 3, 920 participants in the Multi-Ethnic Study of Atherosclerosis (MESA) study who had ≥2 BP measurements during the first 5 years of MESA and had eGFR measurements at both year 5 and 10. Change in BP was estimated as the annualized slope of BP between year 0 and 5 based on linear mixed models (mean number of measurements = 4.0). Participants were then grouped into 1 of 3 categories based on the distribution of systolic BP (SBP), diastolic BP (DBP), and pulse pressure (PP) change (top 20%, middle 21–79%, bottom 20%). We calculated eGFR from cystatin C (ml/min/1.73 m 2 ), estimated annual change in eGFR (ml/min/1.73 m 2 /year), and defined rapid kidney function decline as a >30% decrease in eGFR from year 5 to 10. We used multivariable logistic regression adjusting for year 0 demographic and clinical characteristics, including eGFR and BP, to determine associations of BP change with rapid kidney function decline. RESULTS: Median age was 59 [interquartile range (IQR): 52, 67] and median eGFR at year 0 was 95.5 (IQR: 81.7, 105.9) ml/min/1.73 m 2 . Median SBP at year 0 was 111, 121, and 147 mm Hg for increasing, stable, and decreasing SBP change, respectively. Increasing SBP and widening PP change were each associated with higher odds of rapid kidney function decline compared with stable SBP and PP groups, respectively [odds ratio, OR 1.7 (95% confidence interval, CI 1.3, 2.4) for SBP; OR 1.4 (95% CI 1.1, 1.9) for PP]. Decreasing SBP was associated with rapid kidney function decline after adjusting for all covariates except for year 0 BP [OR 1.4 (95% CI 1.0, 1.8)], but this association was no longer statistically significant after adjustment for year 0 BP. There were no significant associations between DBP change and rapid decline in the fully adjusted models. Similar findings were seen with annual change in eGFR. CONCLUSIONS: Increasing SBP and widening PP over time were associated with greater risk for accelerated kidney function decline even at BP levels below established hypertension thresholds.